TREATMENT OF TYPE 2 DIABETES WITH METFORMIN - Muydinov Azamat Abdulkhamid Ugli; Yusupova Shakhnoza Kadirzhanovna; Abdurazakova Dilbar Sodikovna (Web of Journals Publishing, 2023)
Metformin is a first line treatment for diabetes. As a positive additional effect, it reduces the risk of vascular pathology and mortality and exhibits a geroprotective effect. The appointment of metformin is a pathogenetic therapy for type 2 diabetes, due to the effect of reducing insulin resistance, increasing peripheral glucose utilization by tissues, reducing gluconeogenesis and reducing glucose production by the liver. Epidemiological and randomized studies have shown that long-term treatment with metformin significantly increases the risk of decreased blood levels of vitamin B12 and the risk of folate deficiency, contributing to the progression of diabetic peripheral neuropathy..